Jet Groutıng Yöntemi İle Zeminlerin İyileştirilmesi - Özalp, Hüsnü Korhan (Fen Bilimleri Enstitüsü, 2015)
Geoteknik Mühendisliğinde zemin iyileştirme yöntemleri, gevşek veya yumuşak zeminlerin mühendislik özelliklerini geliştirmek için inşaat öncesi veya sonrasında yaygın olarak kullanılmaktadır. Son on yılda zemin iyileştirme yöntemleri üzerinde yoğun çalışmalar ve ilerlemeler olmuştur. Jet grout teknolojisi, temellerin oturmasını sınırlandırmak, kontrol etmek ve bir dereceye kadar sıvılaşma riskini azaltmak için son yıllardaki gelişimden etkilenen ve günümüzde sıkça kullanılan bir zemin iyileştirme yöntemi olarak tanımlanabilir. Bu tez çalışmasında, jet grout teknolojisinin uygulama yöntemleri, uygulama alanları, avantaj ve dezavantajları incelenmiş ve jet grout kolonlarının imalatı sırasında yapılan kalite kontrol deneyleri konu edilmiştir. Çalışmada ayrıca, zayıf zemin koşulları yüzünden oturma yapan bir bina altındaki jet grout uygulaması incelenmiştir. Bu uygulama sırasında karşılaşılan sorunlar ve alınan önlemler ile enstrümentasyonun önemi konu edilmiştir.

Soil improvement techniques are widely used in geotechnical engineering to develop the engineering properties of loose or soft soils before or after construction. There have been extensive developments in this context during the previous decade. Jet grouting technology, which has also been effected from these developments, is one of the most common soil improvement techniques in order to control and limit excessive settlements of the foundations and in some to reduce the risk of liquefaction. In this thesis; application methods, application range, advantages and disadvantages of jet grouting are presented as well as the quality control tests carried out during jet grout installation. The study also discusses a jet grouting application performed under a building subjected to differential settlement due to poor soil conditions. Troubles and precautions taken against these encountered problems during the jet grouting application were also subjected to this thesis as well as the importance of monitoring for the success of such kind of an application.
Soil Improvement Using Jet Grouting Technology
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2003
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2003
Keywords: Anahtar Kelimeler: Zemin İyileştirme; Jet Grouting; Kalite kontrol; Soil Improvement; Jet Grouting; and Quality Control